THE CORRELATION BETWEEN COGNITIVE READING STRATEGIES AND STUDENTS’ ENGLISH PROFICIENCY TEST SCORE - Yoani Gustanti; Mutiara Ayu (Journal of English Language Teaching and Learning, 2021)
One of the factors that influence the success of language learning is learning strategy, with language learning strategies learners not only get learning achievement, but also can improve language skills. This study aims to determine whether there is a correlation between cognitive reading strategies and English proficiency test scores. The population of this research was the third year students of the Department of English Education at private University. Quantitative methods were used to collect data. A self-report questionnaire consisting of 25 items was administered to 40 students. The reading strategy was evaluated under three headings: pre-reading, while-reading, and post-reading in both sections. The data collected from the questionnaire were statistically analyzed using SPSS. The result of this study indicated that there were positive correlation between cognitive reading strategies and English proficiency test scores. Students were usually and sometimes used cognitive reading strategy while reading a text.